Image, satisfaction, destination and product post-visit behaviours: How do they relate in emerging destinations? - Marques, C.; Vinhas da Silva, R.; Antova, S. (Tourism Management, 2021)
This study proposes a conceptual model that sheds light on how the destination image of emerging tourist destinations relates to tourism satisfaction and intention to subsequently recommend the place and purchase its products. Destination image is studied through three components – cognitive, affective, and unique. Unique image has been overlooked in previous research and few studies focus on its measurement. This study uses a new method of measuring it through text-mining of user-generated blog posts. Findings from a sample of 314 foreign visitors to Sofia, Bulgaria, reveal that the affective image influences tourist satisfaction and post-visit behaviour; the cognitive component has a significant effect on all the constructs, except for tourist satisfaction, whereas unique image only influences the intention to recommend and purchase destination country products. Joining together two streams of research, this study also argues that the intention to recommend a destination spot influences the intention to buy its products.This study proposes a conceptual model that sheds light on how the destination image of emerging tourist destinations relates to tourism satisfaction and intention to subsequently recommend the place and purchase its products. Destination image is studied through three components – cognitive, affective, and unique. Unique image has been overlooked in previous research and few studies focus on its measurement. This study uses a new method of measuring it through text-mining of user-generated blog posts. Findings from a sample of 314 foreign visitors to Sofia, Bulgaria, reveal that the affective image influences tourist satisfaction and post-visit behaviour; the cognitive component has a significant effect on all the constructs, except for tourist satisfaction, whereas unique image only influences the intention to recommend and purchase destination country products. Joining together two streams of research, this study also argues that the intention to recommend a destination spot influences the intention to buy its products.